Achievement of regioselectivity in transition metal-catalyzed direct C–H (hetero)arylation reactions of heteroarenes with one heteroatom through the use of removable protecting/blocking substituents or traceless directing groups. Issue 15 (14th April 2016) - Rossi, Renzo; Lessi, Marco; Manzini, Chiara; Marianetti, Giulia; Bellina, Fabio
Graphical abstract: